2014
DOI: 10.1002/adma.201401490
|View full text |Cite
|
Sign up to set email alerts
|

All‐Polymer Bulk Heterojuction Solar Cells with 4.8% Efficiency Achieved by Solution Processing from a Co‐Solvent

Abstract: All-polymer solar cells with 4.8% power conversion efficiency are achieved via solution processing from a co-solvent. The observed short-circuit current density of 10.5 mA cm(-2) and external quantum efficiency of 61.3% are also the best reported in all-polymer solar cells so far. The results demonstrate that processing the active layer from a co-solvent is an important strategy in achieving highly efficient all-polymer solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
157
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 40 publications
(31 reference statements)
3
157
0
Order By: Relevance
“…Although the range of R g is narrow for our blends owing to the computationally-limited short chains, the trends are apparent and expected to become more pronounced when longer chains and larger system sizes are 26 modeled. Extended chains in the blend morphology can be more favorable in solar-cell operation as they can bridge segregated ordered domains as "tie-chains," and facilitate more efficient pathways for charge carriers to reach electrodes.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Although the range of R g is narrow for our blends owing to the computationally-limited short chains, the trends are apparent and expected to become more pronounced when longer chains and larger system sizes are 26 modeled. Extended chains in the blend morphology can be more favorable in solar-cell operation as they can bridge segregated ordered domains as "tie-chains," and facilitate more efficient pathways for charge carriers to reach electrodes.…”
mentioning
confidence: 92%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Having a greater selection of donor:acceptor pairs can improve our basic understanding of how features in chemical structure affect each device characteristic, and in particular the formation of the BHJ morphology. Representative nonfullerene acceptors include naphthalene 18 and perylene 19 diimides, oligothiophenes, diketopyrrolopyrroles, vinazenes, rhodamines, and substituted pentacenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30 ] Several reports demonstrated that the elaborate selection of processing solvents is an effi cient method in realizing favorable morphologies in All-PSCs. [31][32][33][34][35] In 2011, Tajima and co-workers introduced solvent mixtures based on toluene and o -xylene as processing solvents to fabricate PDI polymer-based All-PSCs that achieved higher PCEs relative to those of devices utilizing conventional solvents, such as chlorobenzene (CB), produced in parallel. [ 35 ] Although an optimistic trend emerged in this work, the achieved PCEs (≈2%) still remained low at that time.…”
Section: Introductionmentioning
confidence: 99%
“…By mixing a few volume percent of processing additives with the host solvent, dichlorobenzene (DCB) or chlorobenzene, the efficiencies of many polymers can be improved dramatically. 11,12 According to these works, it can be concluded that crystallinity as well as domain size in the blends can be tuned effectively by using solvent additive mixtures. Thus, processing additives play an important role in high performance solar cells.…”
mentioning
confidence: 99%